PERAN KOMUNITAS DONASI KREASI DALAM MEMBANGUN KEPEDULIAN SOSIAL WARGA WIYUNG KOTA SURABAYA - Kristiawardani, Novalita; Listyaningsih, Listyaningsih (Kajian Moral dan Kewarganegaraan, 2023)
This study aims to describe the role of the Creative Donation Community in building social care for Wiyung residents in Surabaya. This type of research is qualitative with descriptive method. The theory used in this study is the role theory of Biddle and Thomas. In Biddle and Thomas role theory, there are five types of behavioral roles in society, namely expectation, norm, performance, evaluation, and sanction. Data collection techniques in this study used participatory observation, interviews, documentation and data analysis. The informants in this study were six people from one head of the Creative Donation Community and five members of the Creative Donation Community. Informants were determined using a purposive sampling technique. The results of this study indicate that the role of the Creative Donation Community in building social care for Wiyung residents in the city of Surabaya is first by conducting socialization from house to house residents. Second, carry out social activities to set an example for residents. The third invites residents to work together to build reading hurts.The fourth invites residents to help other residents affected by the disaster. Fifth, foster a positive image of citizens in various social activities. Keywords: Role, Community Creative Donation, Social Care